Humanized care of the nursing professional related to bioetical principles in patients of Victor Ramos Guardia Hospital, Huaraz, 2022 - Julca-Lázaro, Martina Odilia (2024)
Humanized care by nursing professionals becomes a necessary professional clinical practice that allows, through care, that patients have a better quality of life. Therefore, the objective of the research was to determine the relationship between humanized care by nursing professionals and bioethical principles in patients at the Victor Ramos Guardia Hospital in Huaraz. A quantitative approach was used in the methodology; due to its purpose, the type of research was applied; due to its scope, correlational; and because it is non-experimental, a cross-sectional design was used. The population consisted of patients hospitalized in the Surgery, Medicine and Gynecology-Obstetrics services, in a total of 812 patients; a sample of 127 patients was used, the technique used was the survey and the instrument, the questionnaire. The results showed globally that 35.4% think that humanized care is regular and that bioethical principles are sometimes applied; in the opinion of 54.3% and 85.5%, the principles of autonomy and justice are applied respectively. and, in the opinion of 52% and 68.5%, beneficence and non-maleficence are sometimes applied, respectively. Conclusion: the humanized care of the nursing professional has a positive and significant relationship with the bioethical principles in hospitalized patients.